Perancangan Website Pada Cathering Carcinos Kitchen - Atina Fahma Rosyada; Damar Wicaksono; Dimas Nugroho; Thoyyibah Tanjung (CV. Multi Kreasi Media, 2022)
The development of information systems in this era is increasingly advanced, with this business design in the catering sector that serves the sale of food products can also take advantage of information technology such as websites in order to compete and advance. Carcinos Kitchen is a home based business engaged in catering. Carcinos Kitchen's Cathering business is located in the Bumi Sani Permai area, Setia Mekar, Tambun Selatan, Bekasi which only sells products around business locations with a limited scope, obviously it will be difficult to develop, so there needs to be innovation through technology so that the catering business can progress. It was developed using the SDLC (Software Development Life Cycle) method of the Waterfall model. The results of this study state that with website planning it can be run smoothly and also responsively. The website can be used by Carcinos Kitchen as their store information system without any problems. Therefore, the author intends to create a website that can improve promotion and communication between customers and sellers, so as to increase the development of the catering business, and can process the development of attractive websites and increase work productivity.